The Importance of Protein Fingerprints in Bacterial Identification: The Maldi-Tof Technique - Haider, Ali; Ringer, Marianna; Kotroczó, Zsolt; Mohácsi-Farkas, Csilla; Kocsis, Tamás (Journal of Environmental Geography, 2023)
The available literary sources suggest the general applicability and benefits of the Matrix-assisted laser desorption/ionization (MALDI) time-of-flight (TOF) mass spectrometry (MS) in the field of microbiological identification including food quality and safety, and the clinical field. Due to its high reliability, MALDI-TOF might generally be the alternative to the sequence-based and serological-based methods. The essence of the technique is to map the unique protein pattern of microbes that contributes to characterizing a wide variety of microorganisms, including bacteria, fungi, and viruses. On the other hand, these applications only have reliable results under certain conditions (homogeneous infection, adequate cell count, appropriate separation technique). In this review, we focused on the application of MALDI-TOF MS for the environmental field where it has significant potential in the identification, differentiation, and categorization of environmental samples which includes (soil, water, and air), furthermore, some challenges, especially in case of the extreme conditions environment and summarize developments that have been enabled for routine application in the field of environment.